Immunometabolic integration in therapeutic strategies for managing MASLD - González-Serrano, Sergio; Onoiu, Alina-Iuliana; Camps, Jordi; Joven, Jorge (Frontiers in Pharmacology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is clinically complex. Management approaches have focused on addressing the traits of metabolic syndrome and promoting weight loss. However, current treatment options are inadequate, leaving key disease-driving factors unaddressed. Evidence suggests that immune dysregulation determines disease trajectory. Metabolic pathways shape the immune landscape, and the immune system influences metabolic homeostasis. Developing therapies that integrate metabolic correction with immune restoration is essential. We review current available strategies and discuss areas where further research is needed to design drugs and therapeutic combinations that mitigate the complex metabolic and inflammatory interactions driving obesity-associated chronic liver disease. The immunomodulatory effects of obesity-focused interventions remain poorly understood. Bariatric surgery and incretin-based therapies can reduce body fat while reprogramming the hepatic immune environment. Metabolic modulators can reduce lipotoxicity, suppress harmful cytokine networks, and promote reparative immune responses. Other strategies include blocking danger-signaling pathways, modulating chemokine axes, and using cellular therapies. The goal is to interrupt pro-inflammatory amplification cascades and preserve reparative immune cell populations, redefining therapeutic possibilities for liver diseases. Despite advancements in the field, uncertainties still exist regarding the immunometabolic integration. Ongoing clinical trials and the recent approval of two drugs for treating this condition will provide valuable real-world insights in the future about the long-term safety and effectiveness of potentially more accurate treatment approaches. Moreover, causal and clinical biomarkers are being investigated to enhance the diagnosis and management of the significant challenges associated with MASLD-related cirrhosis. Prioritizing and initiating treatment earlier are key factors for achieving successful outcomes.